Buffer usability in a complex world: Interactions between macroprudential regulation and the resolution framework - Balázs Zsámboki; Jakub Doležal; Jaspal Singh; Georg Leitner; Stamatis Vasilakos (European Central Bank (ECB), 2025)
This paper explores the interplay between the risk- and leverage-based prudential and the resolution frameworks within the EU banking system. The prudential framework is designed to enhance the resilience of both individual banks and the banking sector as a whole. It does so by imposing minimum capital requirements and capital buffers that can absorb losses during periods of financial stress. Conversely, the resolution framework focuses on ensuring that banks have adequate loss-absorbing and recapitalisation capacity to facilitate an orderly resolution process, thereby safeguarding public funds. The simultaneous use of capital across and within these two frameworks can have an impact on the effectiveness of capital buffers, presenting various challenges for macroprudential authorities. Our analysis shows that overlaps between risk-based and leverage-based requirements within the prudential framework reduce buffer usability to around 65% to 74% of the overall combined buffer requirement. When the resolution framework is also considered, buffer usability further declines to an average of 40% to 50%, depending on the analytical approach employed. Our simulations of buffer usability under different regulatory options discussed in the literature suggest that implementing the final Basel III standards in the EU would significantly increase buffer usability. The paper also analyses the impact of other options that could reduce or eliminate overlaps between capital buffers and other parallel requirements and quantifies the trade-offs between increased buffer usability and the costs of implementation. As resolution requirements are fully phased in as of 2024, the future evolution of buffer usability and the potential challenges for macroprudential authorities will also depend on how banks set their capital targets relative to the parallel frameworks and how they adapt their balance sheet structures to meet prudential and resolution requirements.
Keywords: G21; G28; G32; 330; financial risk; risk management; own resources; banking system; bank resolution; balance sheet; macroprudential policy; capital requirements; buffer usability; banking regulation